DEVELOPMENT OF SCIENCE AND TECHNOLOGY TO REALIZE THE INDUSTRIAL REVOLUTION 4.0 AND THE INTERNET OF THINGS (IOT) IN INDONESIA - IKA WIDIASTUTI; MIRA MIRNAWATI (International Journal of Innovations in Engineering Research and Technology, 2021)
With reference to the above theme, can be expressed purpose of writing the following research: collecting data and information and to find out about the development concept of science and technology in realizing the industrial revolution 4.0 and the Internet of Things (IOT) in Indonesia. The method used is qualitative research. Data collection techniques using literature study undertaken to collect, study the theories, rules, information obtained from the book and review documents in the form of journals, textbooks and papers relating to the research problem. Main findings in research that is through the roadmap making Indonesia 4.0, set strategy for dealing with Industry 4.0 that encourage labor force in Indonesia continues to increase the ability and skills, especially in the use of technology IOT or integrate Internet capabilities with production lines in the industry massively, and utilization of teknlogi digital more optimal in the industry national as Big Data (machine learning), autonomous robots, cybersecurity, cloud, and relevant. This research can be useful for all readers and all the disciplines and industries in order to increase knowledge and insight.The result is expected to be a thought or consideration of alternative materials for decision makers in solving similar problems regarding the industrial revolution 4.0 and IOT. Provide feedback to the relevant institutions in order to further optimize the development of science and technology in realizing the industrial revolution 4.0 and the Internet of Things (IOT) in Indonesia. The rapid development of science and the use of digital technology over the Internet in various fields.With the development of science and technology so as to achieve 4.0 and IOT industrial revolution so as to facilitate the work effectively and efficiently.